α(2)-Adrenergic Agonists Induce Basic Fibroblast Growth Factor Expression in Photoreceptors In Vivo and Ameliorate Light Damage - Wen, Rong (J Neurosci, 1996)
We observed an induction of basic fibroblast growth factor (bFGF) mRNA in the rat retina after systemic administration of the α(2)-adrenergic agonists xylazine and clonidine. A single injection of xylazine or clonidine transiently increased bFGF mRNA. Preinjection of yohimbine, an α(2)-adrenergic antagonist, completely inhibited this increase. Higher dosage of yohimbine inhibited the baseline expression of bFGF. Of particular interest is the finding that the induced bFGF expression occurred almost exclusively in the inner segment region of photoreceptors. No increase in bFGF mRNA was found in the brain after either xylazine or clonidine injection. Xylazine or clonidine given systemically before and during constant light exposure also reduces photoreceptor degeneration in albino rats. These results indicate that regulation of bFGF expression in photoreceptors is unique in the CNS and suggest that endogenous bFGF promotes photoreceptor survival.